Atelier de réflexion sur les méthodologies de prévision des caractéristiques de la saison pluvieuse on Afrique de l'Ouest et la planification des forums de prévision saisonnières 2012 - Ndiaye, Ousmane (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
Report from workshop on methodologies for predicting West African rainy season characteristics and planning for seasonal forecasts in 2012.